Cobalt tungsten phosphide with tunable W-doping as highly efficient electrocatalysts for hydrogen evolution reaction - Zhang, Bowei (2022)
It has been of interest in seeking electrocatalysts that could exercise equally high-efficient and durable hydrogen evolution upon nonselective electrolytes in both acidic and alkaline environments. Herein, we report a facile strategy to fabricate cobalt tungsten phosphides (CoxW2−xP2/C) hollow polyhedrons with tunable composition based on metal-organic frameworks (MOFs) template method. By the deliberate control of W doping, the synthesized catalyst with the composition of Co0.9W1.1P2/C is found to be able to achieve a current density of 10 mA·cm−2 at overpotentials of 35 and 54 mV in acidic and alkaline media, respectively. This combined electrochemical property stands atop the state-of-the-art electrocatalyst counterparts. To unveil the peculiar behavior of the structure, density functional theory (DFT) calculation was implemented and reveals that the surface W-doping facilitates the optimization of hydrogen absorption free energy (ΔGH*) as well as the thermodynamic and kinetics barriers for water dissociation, which is coupled with the hollow structure of Co-W phosphides, leading to the prominent HER catalytic performance.